Instagram Ads Optimization Strategy to Increase Brand Awareness at CV Media Computindo - Anom, Khotimah Dewi; Khayati, Fajar Nur; Adna, Evania; Oktaviani, Tia; Tarwoto, Tarwoto (International Journal of Informatics and Information Systems, 2023)
This study aims to investigate Instagram Ads optimization strategies in increasing brand awareness at CV Media Computindo. In this ever-evolving digital era, Instagram is one of the most popular and effective marketing platforms. Strong brand awareness is very important for CV Media Computindo because it can increase brand exposure in a competitive market. The research method used is a qualitative approach with descriptive methods. A qualitative approach with a descriptive method is a research method that utilizes qualitative data and is described descriptively. The purpose of qualitative descriptive research is to make systematic descriptions, drawings, or drawings as well as the relationships between the phenomena being investigated. 98% ad reach has been obtained, 100% broadcast is male gender, 78% aged 35-44 years and 21.9% aged 45-54 years, the top locations for exposure are West Java 29.4%, East Java 23, 3%, Jakarta 21.5%, Central Java 21.2%, and DI Yogyakarta 4.4%. Shows that Instagram Ads have a significant influence on building brand awareness at CV.Media Computindo.